x+y = 14
x-y = -24
2x = -10
x = -5
-5 + y = 14
y = 19
2007-05-30 07:44:52
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
Let the integers be x and y.
x+y = 14 ---(1)
x-y = -24 ---(2)
(1)+(2):
2x = -10
x = -5
Sub x=-5 into (1),
x+y = 14
-5 + y = 14
y = 14+5
y = 19
The two integers are -5 and 19.
2007-05-30 13:37:37
·
answer #2
·
answered by Kemmy 6
·
0⤊
0⤋
Let x be one integer and y the other
x + y = 14
y = 14 - x
x - y = -24
Substute in the value for y
x - (14 - x) = -24
2x - 14 = -24
x = -5
-5 + y = 14
y = 19
.
2007-05-30 07:49:18
·
answer #3
·
answered by Robert L 7
·
1⤊
0⤋
x + y = 14; x - y = -24
let y = 14 - x
x - (14 - x) = -24
x - 14 + x = -24
2x = -24 + 14
2 x = -10
x = -5
to get y
y = 14 - x
y = 14 - (-5)
y = 14 + 5
y = 19
Therefore the two integers are - 5 and 19
2007-05-30 07:47:20
·
answer #4
·
answered by Jon 5
·
2⤊
0⤋
You need to set up simultaneous equations. For the unknown quantities I shall use x and y.
From the question we have:
x + y = 14 (equation 1)
and
x - y = -24 (equation 2)
Add those two together and you get:
x + y + x - y = -10
tidy it up:
2x = -10
therefore
x = -5
plug that into equation 1:
-5 + y = 14
Therefore
y = 19
so x = -5 and y = 19
2007-05-30 07:51:53
·
answer #5
·
answered by Red Rose 7
·
1⤊
0⤋
let the two integers be x and y.
then x+y=14 ------(1)
x-y=-24 --------(2)
(1)+(2) gives,
2x=14-24=-10
i.e.x=-5
Substitute this value in (1) we get,
-5+y=14
i.e. y=14+5=19
Therefor the two integers are -5 and 19.
(You can check this by substituting values to the equations)
2007-05-30 13:20:08
·
answer #6
·
answered by hirunisha 2
·
0⤊
0⤋
x + y = 14 ----- (1)
x - y = -24 -----(2)
solve the system of equation
(1) + (2)
2x = 14 - 24 = -10
x = -5
y = 14 - (-5) = 19
2007-05-30 07:49:59
·
answer #7
·
answered by Anonymous
·
1⤊
0⤋
x + y = 14
x - y = -24
2x = -10
x = -5
Since x = -5, y = 19
Now we will check our numbers
Sum is 14 Difference is -24
-5 + 19 = 14, and -5 - 19 = -24
2007-05-30 07:48:04
·
answer #8
·
answered by Stanley D 2
·
2⤊
0⤋
let the first be x and the second be y
x + y = 14
x - y = -24
Add both equations together:
2x=-10
x = -5
substitute into both equations:
-5 + y =14
y = 19
-5 - y = -24
-y = -19
y = 19
-5, 19 answer.
2007-05-30 07:53:23
·
answer #9
·
answered by Dave B. 4
·
1⤊
0⤋
x + y = 14
x - y = -24
2x = -10
x = -5
-5 + y = 14
y = 19
-5 and 19
2007-05-30 07:44:56
·
answer #10
·
answered by 7
·
1⤊
0⤋